2010
DOI: 10.1063/1.3499608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metal/substrate interfaces on radio-frequency loss in superconducting coplanar waveguides

Abstract: Microscopic two-level systems ͑TLSs͒ are known to contribute to loss in resonant superconducting microwave circuits. This loss increases at low power and temperatures as the TLSs become unsaturated. We find that the loss is dependent on both the substrate-superconductor interface and the roughness of the surfaces. A native, oxide-free interface reduced the loss due to TLSs. However, a rough surface in the CPW gap did not cause more TLS loss, but the overall loss was significantly increased for the roughest sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
67
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 17 publications
8
67
1
Order By: Relevance
“…A prominent resonator decoherence source at low powers has previously been found to be two-level states (TLSs) on the various surfaces. [8][9][10][11][12] Knowing TLS locations is important to improve the resonators. Previous measurements and simulations suggested that the exposed metal surface (metal-air interface) is a crucial decoherence source, [9][10][11] driving research in using non-oxidizing superconductors for quantum devices.…”
mentioning
confidence: 99%
“…A prominent resonator decoherence source at low powers has previously been found to be two-level states (TLSs) on the various surfaces. [8][9][10][11][12] Knowing TLS locations is important to improve the resonators. Previous measurements and simulations suggested that the exposed metal surface (metal-air interface) is a crucial decoherence source, [9][10][11] driving research in using non-oxidizing superconductors for quantum devices.…”
mentioning
confidence: 99%
“…We can see clearly from Figure 4 that, with increasing temperature, the center frequency shifts to higher value and the resonance dip becomes broader and shallower. Phenomenally, these behaviors can be explained in the framework of the two-level systems (TLSs) theory [22,23], in which the unsaturated TLSs residing on the metal and dielectric surfaces are believed to be a significant loss mechanism. The resonant interaction of TLSs with electric field (microwave) leads to a temperature dependent variation of the substrate dielectric constant.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, the relevant observations could not be explained by the standard MBT. Recently, an approach beyond the MBT has been proposed by considering the coherent effects of the quantized two-level systems [16,[21][22][23] on top of the resonator film due to the existence of native oxides layer [14,16]. Practically, before the measurement, the device has to be exposed to the air environment for preparation, thus a severalnanometer-thick native oxide layer could be formed on top surface of the resonator.…”
Section: Irradiation Saturate Temperatures Of Superconducting Resonatmentioning
confidence: 99%